A study on the Effect of Cooling Capacity in Capillary Ceiling Radiant Cooling Panel by usingdifferent Shape Pipe Design & Parameters - Vikas Kumar Patle (AG Volumes, 2021)
In order to obtain surface temperature distributions and cooling capabilities, a computational fluid dynamics (CFD) simulation was carried out on the heat transfer of chilled water flow in the capillary of the ceiling radiant cooling panel. Capillary radiant panel circumstances and transfer performance were complicated by six elements, including chilled water intake parameters, gypsum plaster conditions, and capillary matting structural characteristics. Temperature profiles on ceiling panels may be evaluated using an index of temperature non-uniformity coefficient. The results of the simulation were compared with temperature variation and hydraulic power is calculated in terms of pressure in all 4 cases which are defined in form of different shapes of pipes and variation in gap between each pipe. Pipe having spiral shape with 20 mm spacing between each spirals have the best heat absorptions rate and this design obtain lowest temperature in ceiling which is 17.593.